(3COGA eG hLH ef HjGf hVY GdhVGYjf aj QLHs - (3CHh GdNWGH Hf MSf Hf Ydj Hf CHj GdHSGe GdaGWej GdMSjfj Gdchajs ((3GdeOQSI GdcGedjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY dMOjK eMeO GdeUWai YHOg hQShdg dhGA efKhQGhdeG cKQ GNJdGa GdfGS ai gPG GdTgQ GdeSei HQLH hbd GdYGQa Hg s
(3BNQgG (B:s
(3hjJdhg Ef TGA Gddg eG LGA ai aVd TYHGf hgh GdTgQ GdPi KHJ UjGe QShd Gddg Udi Gddg Ydjg hSde dg hHGfi hcGfJ GdaVjdI ai UjGeg Ydi TgQ QLH fGWbI s
(3Cdag ddSdWGf Gdedc GdcGed Ndjds
(3HCWQGa GdfSNI CKGQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDdas
Keywords: (3GdMOjK h GdeUWdMs